Little mercies [large type] - Gudenkauf, Heather (Thorndike Press, 2014)
Veteran social worker Ellen Moore is a fiercely dedicated children's advocate and a devoted mother and wife. But one blistering summer day, a simple moment of distraction will have repercussions that Ellen could never have imagined, threatening to shatter everything she holds dear, and trapping her between the gears of the system she works for. Meanwhile, ten-year-old Jenny Briard suddenly finds herself on her own, forced to survive with nothing but a few dollars and her street smarts. The last thing she wants is a social worker, but when Ellen's and Jenny's lives collide, little do they know just how much they can help one another.